Parental mediation of the use of the internet: a psychometric study with Portuguese pre-adolescents - Azevedo, Ângela Sá (2022)
Individuals start using technological resources, among which the Internet, increasingly earlier in life. Parents are currently challenged to mediate the use of technologies by their sons/daughters, while simultaneously fostering their autonomy and self-regulation. Parental mediation of offspring’s use of the Internet is needed, given its acknowledged risks. This study intends to offer preliminary psychometric evidence on the adaptation and validation of the Parental Mediation Scale (PMS) with Portuguese pre-adolescents. A total of 355 pre-adolescents (55.2% female) aged 10–13 years old (M = 11.20, DP = 0.93) from northern Portugal participated in this study. The PMS was translated from Castilian to Portuguese by two experts in the field and in both languages. Participants completed a sociodemographic questionnaire and the Portuguese PMS version on paper, in groups, and in the classroom setting. Results from confirmatory factor analyses suggested that a revised bi-dimensional measurement model yielded an adequate fit to the sample. Cronbach’s alpha of 0.82 was found for the active/participated mediation and the restrictive mediation PMS subscales. Variations in parental mediation for participants’ sex, and statistically significant relations with participants’ age, use of the Internet, and parents’ educational levels were found. Future studies might recruit broader samples in terms of age, school levels, and geographic areas to add evidence on the psychometric properties of the Portuguese PMS version. Nonetheless, this study might stimulate empirical and practical attention to parental mediation of sons/daughters’ use of the Internet.